Late post-transplant recurrence of an anti-myeloperoxydase antibody-associated vasculitis in a former double-positive patient: a case report - Chenaf-Benabdelmoumene, Nessma; Chabannes, Melchior; Ducloux, Didier; Bamoulid, Jamal; Crepin, Thomas; Lang, Stéphane (Frontiers in Immunology, 2026)
Post-transplant anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) recurrence on the allograft is rare and, to our knowledge, has never been described in the situation of a previous double-positive vasculitis with both ANCA and anti-glomerular basement membrane (GBM) antibodies. We report an unusual case of anti-myeloperoxydase (MPO) antibody-associated vasculitis recurrence occurring 14 years after kidney transplantation following a double-positive anti-GBM and anti-MPO glomerulonephritis. The transplant induction regimen consisted of anti-thymocyte globulin, and initial maintenance therapy associated tacrolimus, mycophenolate mofetil, and corticosteroids. Mycophenolate mofetil was discontinued 4 months after transplantation due to persistent leukopenia, and tacrolimus was maintained along with corticosteroids. At 14 years post-transplantation, the patient presented with diffuse alveolar hemorrhage, acute kidney injury stage 1 of Kidney Disease Improving Global Outcomes, proteinuria, microhematuria, serous otitis media and anti-MPO antibodies resurgence, without detectable anti-GBM antibodies. A kidney allograft biopsy was performed and showed rare active crescents with severe chronic injuries. This pulmonary and renal involvement was attributed to an anti-MPO antibody-associated vasculitis recurrence. The induction treatment of the relapse consisted of methylprednisolone at 5 mg/kg and rituximab at 375 mg/m2 per week for 4 weeks. Renal function remained stable, urinary protein to creatinine ratio decreased from 0.9 g/g to 0.3 and 0.2 g/g at 6 and 12 months, respectively. Microhematuria resolved at 6 months and remained absent subsequently. Maintenance treatment was continued with rituximab every 6 months. According to the literature, post-transplant isolated AAV recurrence on the allograft remains exceptional, ranging between 0.003 and 0.076 per patient per year. To our knowledge, there are no reported cases of post-transplant anti-MPO-associated vasculitis recurrence in a patient with former anti-MPO and anti-GBM antibody-associated vasculitis. This case underlines the fact that AAV can recur late after transplantation in previously double-positive vasculitis patients. Thus, close monitoring of clinical and biological signs of recurrence is necessary in these patients. Because the pathophysiology of this atypical entity remains unclear, further trials are still necessary to highlight the underlying mechanisms of this particular auto-immune association and, more specifically, of isolated post-transplant AAV recurrence in double-positive patients to improve prevention and to elaborate more efficient immunosuppressive strategies.